Stress-Induced Locomotor Sensitization to Amphetamine in Adult, but not in Adolescent Rats, Is Associated with Increased Expression of ΔFosB in the Nucleus Accumbens - Carneiro de Oliveira, Paulo E.; Leão, Rodrigo M.; Bianchi, Paula C.; Marin, Marcelo T.; Planeta, Cleopatra da Silva; Cruz, Fábio C. (Frontiers in Behavioral Neuroscience, 2016)
While clinical and pre-clinical evidence suggests that adolescence is a risk period for the development of addiction, the underlying neural mechanisms are largely unknown. Stress during adolescence has a huge influence on drug addiction. However, little is known about the mechanisms related to the interaction among stress, adolescence and addiction. Studies point to ΔFosB as a possible target for this phenomenon. In the present study, adolescent and adult rats (postnatal day 28 and 60, respectively) were restrained for 2 hours once a day for 7 days. Three days after their last exposure to stress, the animals were challenged with saline or amphetamine (1.0 mg/kg i.p.) and amphetamine-induced locomotion was recorded. Immediately after the behavioral tests, rats were decapitated and the nucleus accumbens was dissected to measure ΔFosB protein levels. We found that repeated restraint stress increased amphetamine-induced locomotion in both adult and adolescent rats. Furthermore, in adult rats, stress-induced locomotor sensitization was associated with increased expression of ΔFosB in the nucleus accumbens. Our data suggest that ΔFosB may be involved in some of the neuronal plasticity changes associated with stress induced-cross sensitization with amphetamine in adult rats.